The role and development status of Dipterocarpaceae family in Lao PDR - Phongoudom, Chanhsamone (Institut Penyelidikan Perhutanan Malaysia, 2005)
This paper discusses the roles and status of Dipterocarpaceae family in the country, focusing on the socio-economic contributions in terms of timber, sawn woods, plywood production, non-timber forest products and other uses of species in the family. The paper also reviews the status of the dipterocarp forests in terms of forest areas, distribution, occurrences, status of conservation, as well as the domestication, nursery practice, taxonomy, and seed sources of species in the family of Dipterocarpaceae in Lao PDR.